A qualitative study of the childbearing experience of women living with multiple sclerosis. (June 2013) - Kosmala-Anderson, Joanna; Wallace, Louise M.
<x xml:space="preserve">Abstract</x> Purpose: Although at any time in the UK, there are about 20, 000 women with MS who may be considering having children, healthcare system often fails to provide them with information and support they need to make informed decisions about their health and pregnancy management. The aim of this paper is to explore the childbearing experience of women with MS to determine what support and information may be useful to this target group. Method: Interviews were conducted with women with MS (n = 9). Transcripts were analysed using thematic analysis. Results: Three major themes emerged from the interviews with women living with MS. We found women were concerned about both medical and practical issues associated with having children. Limited access to information about relationships between MS and childbearing and receiving conflicting or wrong information was recounted. Opinions of family members and clinicians regarding having children in the context of MS impacted on women's experience of making decision about having children and childbearing. Conclusions: Women with MS can benefit from having access to comprehensive, structured sources of information about MS and childbearing. Healthcare professionals and family members 'support could be channelled more appropriately to enhance their experience of making choices about childbearing.